Gambaran Wabah Dalam Karya Sastra Metamorphoses, The Good Earth, The Seventh Seal, Dan Cat’s Cradle: Kajian Interteks - Erwany, Lela; Nasution, Zuraidah; Rosliani, Rosliani; Sari, Syafriani Tio (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This paper aims to analyze patterns and causes of epidemics in the novels Metamorphoses, The Good Earth, The Seventh Seal, and Cat’s Cradle. Through the approach of intertextual theory and the hermeneutic method, common patterns are identified, namely family disintegration, unnatural births, and epidemics. The cause of these epidemics is infidelity or deviation within the family, seen as a divine punishment upon humanity. These findings highlight the relationship between literary texts and social phenomena, offering insights into how literary narratives reflect and shape our understanding of epidemics and human behavior. The implications of this analysis can provide a deeper understanding of human complexity and the relevance of literature in illuminating significant aspects of human experience, such as epidemics and morality.